Painter IX creativity : - Sutton, Jeremy (Focal Press/Elsevier, 2005)
Corel Painter, the world’s leading natural-media painting software, has long been a favorite among fine artists and illustrators, who love the way it emulates the experience of working with traditional media such as watercolor, oils, pastel, pencil, and ink, yet with all the advantages of a digital technology. Whether you're an experienced digital artist or an artist who needs a bridge from traditional media to electronic art, there's no better way to learn Painter than from longtime Painter artist and instructor, Cher Threinen-Pendarvis.